Penggunaan Bibiloshyni dalam Analisis Tren Penelitian Keinovatifan Guru - Febriyanti, Chatarina; Suharyati, Henny; Sunaryo, Widodo (SAP (Susunan Artikel Pendidikan), 2025)
This literature study aims to observe the trend of scientific article publications published by Scopus on the theme of teacher innovation so that the projection or prediction of other relevant variables to be linked to the theme of teacher innovation research can be seen. The method used in this literature study involves several steps: 1) mining data from scientific article publications originating from Scopus, 2) filtering where only those from journals are used, while those from proceedings, books, or book chapters are not used, 3) using R studio, namely biblioshiny, to process the obtained data, 4) conducting analysis and interpretation of the results from biblioshiny. The results of the study found that publications related to the theme of teacher innovation originating from Indonesia in Scopus journals are still relatively few. Therefore, teacher innovation research is still relevant to be researched, especially in relation to other variables such as learning organization, creativity, self-efficacy, and job satisfaction.